Pemilihan Presiden dan Wakil Presiden secara Langsung - Sunyoto Usman (Unisia, 2004)
Direct presidential election system is not always a guarantee to choose that the choosen leader is always the best to govern this nation, in democration process we find some factors that not always rational and objective to choose the leader, it can depend on subyektif emotional factors which liebehind the primordialisme and also, we can't neglect the factor of personal benefit orientation as a result of money politics. The election system must encourage that only candidate who have morality, integrity and capabilty and support from the more people that will emerge to bring the good of the society and nations.